Ocean Wave Energy Conversion and Policy Frameworks: A Scoping Review of Technological Readiness, Regulatory Instruments, and Deployment Challenges - Salih, Mildred; Pingay, Tadzmahal (The Indonesian Institute of Science and Technology Research, 2026)
Ocean wave energy represents a promising yet underutilized renewable energy source with significant potential to support global energy transitions, particularly in coastal and island regions. Despite substantial technological progress in wave energy conversion (WEC) systems, large-scale deployment remains limited. The existing literature is predominantly technology-oriented, while systematic syntheses focusing on policy and governance dimensions remain fragmented. This study conducts a policy-oriented scoping review to map the body of research on ocean wave energy conversion, with a particular emphasis on policy instruments, regulatory frameworks, and governance challenges that influence deployment and commercialization. Following the PRISMA Extension for Scoping Reviews (PRISMA-ScR) guidelines, peer-reviewed studies published between 2015 and 2025 were identified from Scopus, Web of Science, and IEEE Xplore. The review results indicate that public research and development funding, technology-specific market incentives, and integrated marine spatial planning are critical enablers of wave energy deployment. Conversely, regulatory complexity, policy instability, and institutional fragmentation remain persistent barriers, especially in developing and archipelagic contexts. This scoping review highlights key policy gaps and underscores the need for coherent, stable, and context-sensitive governance frameworks to facilitate the sustainable commercialization of ocean wave energy.